Estudo da atividade leishmanicida de derivados da Cambretastatina A-4: uma proposta para novas estratégias no tratamento da Leishmaniose - Araújo, Morgana Vital de (2013)
Leishmaniasis are considered a public health issue that affect millions of people. The treatment adopted has a number of adverse effects, various strains of Leishmania drug resistance and high toxicity, which may lead the patient to death. Thus, in order to develop safer and more effective treatments, this work aims to investigate the leishmacidal activity of combretastine A-4 derivatives. Therefore, we performed an initial screening to determine the toxicity on the host cell and on promastigotes. In viability assay, it was observed that LASSBio 1586, 1587, 1588, 1589, 1590, 1592, 1594, 1595 and 1716 derivatives did not show toxic effect to maximum concentration 100 μM. Subsequently, the viabality assay against promastigotes of Leishmania braziliensis, L. amazonensis and L. chagasi was performed. The results obtained in the evaluation of anti-promastigote activity against L. braziliensis showed that LASSBio 1594, 1714, 1715, 1716, 1735, 1738, 1739, 1740, 1741, 1742 and 1744 derivatives exhibited significant leishmanicidal activity. In the test against the growth of promastigotes of L. amazonensis, LASSBio 1594, 1714, 1715, 1716, 1735, 1738, 1739, 1740, 1741, 1742 and 1744 derivatives had activity against parasite. While in the test against the growth of promastigotes of L. chagasi, LASSBio 1586, 1587, 1588, 1589, 1590, 1591, 1592, 1593, 1596, 1715, 1735, 1738 and 1740 derivatives had significant activity against parasite. From the screening were selected two CA-4 derivatives for testing in vivo infection in the ears of BALB / c mice with promastigotes of L. amazonensis, which causes cutaneous leishmaniasis. In this study, it was observed that the animals treated with LASSBio 1738 and LASSBio 1588 derivatives had significant decrease of injury when compared to the control. In this same assay, it was observed that there was no change in liver enzymes alanine transaminase (ALT) and aspartate transaminase (AST), creatinine and urea. However, to examine the spleen, only treatment with LASSBio 1538 did changes the spleen weight significantly. Therefore, we can concluded that CA-4 derivatives are effectives against promastigotes of Leishmania braziliensis, L. amazonensis and L. chagasi. Furthemore, LASSBio 1588 and LASSBio 1738 have effect on the course of infection of the ear in vivo with L. amazonensis at the dose of 30 μmol/kg/days x 28 days (i.p.). Thus, CA-4 derivatives stood out as important substances in the proposed new antileishmanial drugs.